Internet and civil society participation in local governance: The case of Tamil Nadu, India - Fernando, Joseph (Animo Repository, 2004)
Contemporary public governance depends on the capacity of public administrators to effectively manage the public affairs through networks. Electronic networks hold great promises as tools for access to and management of the societal, political and organizational networks. The recent E-Governance initiatives (primarily through the Internet)) of the government of Tamil Nadu, India is generating public interest as to the intentions, feasibility and the ultimate benefits to the end-users. Networking via Internet is becoming more a norm than an exception in the State. As these initiatives transform the public governance from informational stage to interactive stage, new challenges are also emerging in the form of digital inclusion and exclusion. The Civil Society in Tamil Nadu has to come in terms with the digital networking. But the Civil Society is slow and reluctant to adapt to the emerging changes. The highly fragmented and extensively dispersed Civil Society is in urgent need of networking, so as to be responsible stakeholders of public policies. With its enormous presence and influence among the rural population, the Civil Society can promote rural network and connectivity. In fact the Civil Society can be the best catalyst of the emerging ‘networked society’, inclusive of all the citizens, literate or illiterate, urban or rural, affluent or economically backward, socially included or excluded. Such a networked society would be capable of participating in the e-democracy of the new millennium. The ability of the Internet and the capacity of the Civil Society in promoting digital networking and participatory local governance in Tamil Nadu is truly tremendous and worth promoting.